Probiotics are a good choice for the treatment of bacterial vaginosis: a meta-analysis of randomized controlled trial - Rongdan Chen; Rong Li; Wei Qing; Yingxuan Zhang; Zuyi Zhou; Yi Hou; Yiya Shi; Hongwei Zhou; Muxuan Chen (BMC, 2022)
Plain Language Summary Our meta-analysis found that probiotics may play an active role in adjuvant treatment of bacterial vaginosis by conventional antibiotic therapy. It was emphasized that oral administration of L. rhamnose was more effective than vaginal application of L. rhamnose in the treatment of bacterial vaginosis. The therapeutic effect of probiotics varies with the administration route and dosage of probiotics.